Poly(ionic liquid)s based on imidazolium hydrogen carbonate monomer units as recyclable polymer‐supported N‐heterocyclic carbenes: Use in organocatalysis. Issue 21 (30th July 2013) - Coupillaud, Paul; Pinaud, Julien; Guidolin, Nicolas; Vignolle, Joan; Fèvre, Maréva; Veaudecrenne, Ellen; Mecerreyes, David; Taton, Daniel
ABSTRACT Synthesis of novel poly(ionic liquid)s, namely, poly(1‐vinyl‐3‐alkylimidazolium hydrogen carbonate)s, denoted as poly([NHC(H)][HCO3])s or PVRImHCO3, where R is an alkyl group (R = ethyl, butyl, phenylethyl, dodecyl), is described. Two distinct synthetic routes were explored. The first method is based on the free‐radical polymerization (FRP) of 1‐vinyl‐3‐alkylimidazolium monomers featuring a hydrogen carbonate counter anion (HCO3−), denoted as VRImHCO3. The latter monomers were readily synthesized by alkylation of 1‐vinylimidazole (VIm), followed by direct anion exchange of 1‐vinyl‐3‐alkylimidazolium bromide monomers (VRImBr), using potassium hydrogen carbonate (KHCO3) in methanol at room temperature. Alternatively, the same anion exchange method could be applied onto FRP‐derived poly(1‐vinyl‐3‐alkylimidazolium bromide) precursors (PVRImBr). All PVRImHCO3 salts proved air stable and could be manipulated without any particular precautions. They could serve as polymer‐supported precatalysts to generate polymer‐supported N‐heterocyclic carbenes, referred to as poly(NHC)s, formally by a loss of "H2CO3" (H2O +CO2) in solution. This was demonstrated through selected organocatalyzed reactions of molecular chemistry, known as being efficiently mediated by molecular NHC catalysts, including benzoin condensation, transesterification and cyanosilylation of aldehyde. Of particular interest, recycling of the polymer‐supported precatalysts was possible by re‐carboxylation of in situ generated poly(NHC)s. Organocatalyzed reactions could be performed with excellent yields, even after five catalytic cycles. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4530–4540